Endovascular retrieval of dental needle retained in the internal carotid artery. (12th April 2017) - Moore, Kenneth; Khan, Nickalus R; Michael, L Madison; Arthur, Adam S; Hoit, Daniel
Abstract : Intravascular foreign bodies are a known complication of medical and dental procedures. Dental anesthetic needles may be broken off and retained in the oropharynx. These needles have occasionally been reported to migrate through the oral mucosa in to deeper structures. Here we present the case of a 57-year-old man who had a retained dental needle that had migrated into his internal carotid artery. The needle was removed using endovascular techniques. To our knowledge, this is the first report of a retained dental needle being retrieved using this method. We review the literature on intravascular foreign bodies, retained dental needles, and endovascular techniques for retrieval of such foreign bodies.